2019
DOI: 10.23887/ijssb.v3i2.17644
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Indikator Kinerja Ekonomi, Indikator Kinerja Lingkungan dan Indikator Kinerja Sosial terhadap Profitabilitas Perusahaan Manufaktur

Abstract: Berdasarkan standar GRI G.4, item-item pelaksanaan CSR terbagi menjadi tiga fokus utama, yaitu indikator kinerja ekonomi, indikator kinerja lingkungan dan indikator kinerja sosial. CV. Suien Insan Persada merupakan perusahaan yang bergerak pada bidang manufaktur, sehingga perusahaan diwajibkan untuk melaksanakan indikator kinerja CSR. Dalam pelaksanaannya CV. Suien Insan Persada tetap memperhatikan tingkat profitabilitas yang diperoleh. Sehingga tujuan dari penelitian ini yaitu ingin mengetahui pengaruh pelaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A similar study conducted by Nawangsari & Ika Nugroho (2019) shows that there are disclosures of the same aspects by different wood processing industries. The study revealed that the wood industry's waste is processed so that it does not cause environmental pollution around the industrial area.…”
Section: Aspects Of Wastewater and Wastementioning
confidence: 67%
See 2 more Smart Citations
“…A similar study conducted by Nawangsari & Ika Nugroho (2019) shows that there are disclosures of the same aspects by different wood processing industries. The study revealed that the wood industry's waste is processed so that it does not cause environmental pollution around the industrial area.…”
Section: Aspects Of Wastewater and Wastementioning
confidence: 67%
“…The following is an excerpt from the disclosure in the WOOD annual report for the years 2017 to 2020: The company's efforts to increase the availability of raw materials have been carried out by securing the supply of raw materials based on international standard policies. (WOOD Annual Report 2017, 2018, 2019 The following is an excerpt from the disclosure regarding the impact of the company's use of raw materials:…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In increasing company profits, companies can effectively and efficiently manage their resources. Research (Putri et al, 2019), (Nawangsari & Nugroho, 2019), (Asjuwita & Agustin, 2020), (Mardiana & Wuryani, 2019) states that environmental performance can increase company profitability. Based on the theory and empirical studies that have been carried out by several researchers, the hypothesis in this study is H4: environmental performance has an influence on company profitability.…”
Section: Relationship Between Environmental Performance With Company Profitabilitymentioning
confidence: 99%
“…The expenditure of tourists certainly contributes to the economic growth of DIY, including its impact on 715 batik SMEs which are spread evenly throughout DIY. Social performance includes several topics, namely labor, human rights, product responsibility, and society and so on (Nawangsari and Nugroho, 2019). Batik SMEs in DIY Province, especially natural color batik SMEs, are reported to have continuously improved their social performance in line with the increasing trend of natural color batik after the Nusantara Batik Title was held by the Indonesian Batik Foundation in 2017.…”
Section: Introductionmentioning
confidence: 99%